(untitled) (Baghdad Science Journal, 2025)
The primitive streak and notochord and previously the anterior marginal crescent (AMC), anterior visceral endoderm (AVE) and the anterior hypoblast (AHB) are embryonic entities which identify main body axes and thus establish body plan in the early stages of embryonic development. All of the anterior pre-gastrulation differentiation structures are addressed terminology as anterior pre-gastrulation differentiation (APD). These structures are defined morphologically and are called in mouse (AVE), in rabbit (AMC) and in the pig (AHB). The anterior hypoblast cells of APD are higher and denser than at the opposite pole of the embryo. Moreover, the APD stretches variously between species and has different shapes in the mammalian embryos, for example, it is crescent-like shape in the rabbit and disc-like shape in the pig. In this study, the sox17 expression patterns show that the anterior pole of rabbit is differentiated genetically prior to morphological differentiation. In Situ hybridization signals of sox17 are located in AMC area at early pre-gastrulation stages before appearance of first cellular differentiation signs. This study fixes sox17 gene as one of the important genes in definition of the polarity of the mammalian embryo before appearance morphological or axial landmarks.